CYLD destabilizes NoxO1 protein by promoting ubiquitination and regulates prostate cancer progression. (28th January 2022) - Haq, Saba; Sarodaya, Neha; Karapurkar, Janardhan Keshav; Suresh, Bharathi; Jo, Jung Ki; Singh, Vijai; Bae, Yun Soo; Kim, Kye-Seong; Ramakrishna, Suresh
Abstract: The NADPH oxidase (Nox) family of enzymes is solely dedicated in the generation of reactive oxygen species (ROS). ROS generated by Nox are involved in multiple signaling cascades and a myriad of pathophysiological conditions including cancer. As such, ROS seem to have both detrimental and beneficial roles in a number of cellular functions, including cell signaling, growth, apoptosis and proliferation. Regulatory mechanisms are required to control the activity of Nox enzymes in order to maintain ROS balance within the cell. Here, we performed genome-wide screening for deubiquitinating enzymes (DUBs) regulating Nox organizer 1 (NoxO1) protein expression using a CRISPR/Cas9-mediated DUB-knockout library. We identified cylindromatosis (CYLD) as a binding partner regulating NoxO1 protein expression. We demonstrated that the overexpression of CYLD promotes ubiquitination of NoxO1 protein and reduces the NoxO1 protein half-life. The destabilization of NoxO1 protein by CYLD suppressed excessive ROS generation. Additionally, CRISPR/Cas9-mediated knockout of CYLD in PC-3 cells promoted cell proliferation, migration, colony formation and invasion in vitro . In xenografted mice, injection of CYLD-depleted cells consistently led to tumor development with increased weight and volume. Taken together, these results indicate that CYLD acts as a destabilizer of NoxO1 protein and could be a potential tumor suppressor target for cancer therapeutics. Highlights: DUB-Knockout library identifies CYLD negatively regulating NoxO1 protein expression. CYLD destabilizes NoxO1 by enhancing its ubiquitination and thus reducing its half-life. Loss of CYLD promotes NoxO1 expression in prostate cancer and elevates NoxO1-mediated ROS production. CYLD depleted prostate cancer cells displayed increased proliferation and metastasis. Loss of CYLD drives NoxO1-mediated pathogenesis of cancer.